Molecular Survey of Piroplasmids and Hemosporidians in Vampire Bats, with Evidence of Distinct Piroplasmida Lineages Parasitizing Desmodus rotundus from the Brazilian Amazon - de Mello, Victória Valente Califre [UNESP]; Calchi, Ana Cláudia [UNESP]; de Oliveira, Laryssa Borges [UNESP]; Coelho, Taciana Fernandes Souza Barbosa; Lee, Daniel Antônio Braga [UNESP]; Franco, Eliz Oliveira [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (My University, 2023)
Although bats can serve as reservoirs for several viruses and bacteria, there is limited knowledge regarding the diversity of apicomplexan protozoan belonging to the Piroplasmida and Haemosporida orders within this group of mammals. The present study aimed to investigate the occurrence and phylogenetic assessment of piroplasmids and hemosporidians in spleen samples collected from 229 vampire bats (228 Desmodus rotundus and 1 Diaemus youngii) in the states of Pará, Roraima, Amapá, and Amazonas, northern Brazil. Out of 229 bat spleen samples, 43 (18.77%) tested positive in a nested PCR for piroplasmids based on the 18S rRNA gene. Thirteen sequences (ranging from 474 to 828 base pairs) of the partial 18S rRNA gene showed 91.04–100% identity to Theileria sp., Babesia sp., and Piroplasmida previously detected in deer, tapirs, opossums, and crab-eating raccoons. The phylogenetic analysis based on the near-complete 18S rRNA gene positioned the obtained sequences from three D. rotundus in distinct clades (Theileria sensu stricto, Tapirus terrestris, and “South America Marsupialia”). All bat spleen DNA samples tested negative in a nested PCR assay for hemosporidians based on the cytB gene. The present study reported, for the first time, the presence Babesia sp. and Theileria sp. DNA in D. rotundus. The distinct positioning of the 18S rRNA gene sequences within different clades demonstrates the occurrence of different piroplasmid species in vampire bats.
Keywords: Babesia; common vampire bat; Haemosporida; Theileria